ESTABLISHMENT OF TOUR PACKAGES AND FEASIBILITY OF COSTS WITH NPV IN BARITO TOURISM VILLAGE IN MALANG DISTRICT - Medea Rahmadhani Utomo; Mangku Purnomo; Fitrotul Laili; Mochamad Sufi Chaqqi (Agricultural Socio-Economics Journal, 2023)
Tourism is a driver of the economic sector and a solution for the government to increase economic development. Tourism is one of the important sectors in developing a country because it contributes to job creation and state income and promotes the prosperity of a country. The tourism sector has a multiplier impact on the regional economy. One is that it can help increase people's income and alleviate poverty. There are problems in efforts to develop tourism, and researchers make plans for developing tourist village areas by mapping the potential of tourist destinations and packaging in the form of tour packages. Planning for developing tourist areas in rural areas through innovation in making tour packages from the results of mapping tourism potential will boost regional economic growth and strengthen the community to carry out a sustainable development process. The research was conducted using mixed method analysis, namely descriptive qualitative, and quantitative. Calculation data for the design cost of promotion planning and marketing of tourism villages is calculated using financial feasibility analysis. Financial feasibility analysis is carried out by calculating the NPV (Net Present Value). The planning for packaging the Barito Village tour package is named " Local Pride Tour Of Barito," which is grouped into three types. First, based on the theme with the respective names of the Heritage Tour, Artificial Tour, and Socio-Economic Tour packages. Second, based on age groups with the names of each package, Kids Tour, Teenager Tour, Adult Tour. Third, based on special needs, each package is named Religion Tour, Healing With Nature Tour, and Sports Tour, which has two types of packages named Adventure Trail and Gowes to Barito Village. Based on the results of the NPV calculation, the NPV value of the entire tour package is more than zero, so all tour packages in the Barito Tourism Village Area are feasible.